Opportunity Set, Liquidity, Stock Return, Inflation As A Moderator Investment Risk, Investment - Masno Marjohan; Anggun Anggraini; Sayu Ketut Sutrisna Dewi; Arsid (Jurnal Manajemen, 2023)
This study aims to analyze the influence of liquidity of investment risks, opportunities on stock return with inflation as a moderator. These study was a quantitative study which invloving panel data method. In thid study, data processing and population studies using Eviews software which consist of companies in the banking sector listed on the Indonesia Stock Exchange. This study found that investment risk has no impact on equity returns, the level of investment opportunity is locked into equity returns, liquidity has a significant negative impact on equity returns, and inflation affects the ratio of investment risk to equity returns was found to have the potential to increase Inflation weakens the relationship between investment opportunities and equity returns, while inflation can strengthen the relationship between liquidity and equity returns. It is hoped that further researchers will be able to include these variables as consideration in doing such investigation.